2018
DOI: 10.1101/452813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potentiating α2 subunit containing perisomatic GABAA receptors protects against seizures in a mouse model of Dravet Syndrome

Abstract: Acknowledgements:This work was supported by NIH grants R01 NS084959 (J.A.K.) and R01MH099114 (A.C.) and a seed grant from the American Epilepsy Society (A.C.). We thank Nick Brandon from AstraZeneca for providing AZD7325.Abstract GABA A receptor potentiators are commonly used for the treatment of epilepsy, but it is not clear whether distinct GABA A receptor subtypes contribute to seizure activity, and whether targeting receptor subtypes will have disproportionate benefit over adverse effects. Here we demonstr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 63 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…Finally, modifier genes and pathways can provide novel targets for therapeutics. Previously, we used AZD7325, a GABAA α2/α3selective PAM, to modulate the neuronal phenotype of Scn1a +/mice and showed it had protective effects against hyperthermia-induced seizures (28). The current study confirmed that AZD7325 can be used to distinguish the GABAA receptor type in perisomatic synapses and directly demonstrated that the Edited allele contributes to an enriched α2 subunit content.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Finally, modifier genes and pathways can provide novel targets for therapeutics. Previously, we used AZD7325, a GABAA α2/α3selective PAM, to modulate the neuronal phenotype of Scn1a +/mice and showed it had protective effects against hyperthermia-induced seizures (28). The current study confirmed that AZD7325 can be used to distinguish the GABAA receptor type in perisomatic synapses and directly demonstrated that the Edited allele contributes to an enriched α2 subunit content.…”
Section: Discussionsupporting
confidence: 75%
“…We previously demonstrated that perisomatic inhibitory synapses of hippocampal CA1 neurons had a greater abundance of α2-containing GABAA receptors in 129 mice compared to B6 mice [28(28). α2 GABAA receptor mediated currents can be distinguished by the use of the selective α2/α3 positive allosteric modulator (PAM) AZD7325, which has a larger effect on slowing the decay kinetics of inhibitory postsynaptic currents (IPSCs) enriched in α2 subunits (28). To determine whether the Edited allele affected synaptic GABAA receptors, we recorded perisomatic IPSCs in CA1 neurons in B6/B6 and Edited/B6 mice.…”
Section: Single Nucleotide Repair Of Gabra2 Alters Neuronal Phenotypementioning
confidence: 99%
See 2 more Smart Citations
“…In this edition of The Journal of Physiology , Nomura et al . () explore the importance of α 2 subunit‐containing GABA A receptors in determining seizure severity in a mouse model of Dravet syndrome.…”
mentioning
confidence: 99%